Mobile Interventional Stroke Teams Lead to Faster Treatment Times for Thrombectomy in Large Vessel Occlusion. Issue 12 (December 2017) - Wei, Daniel; Oxley, Thomas J.; Nistal, Dominic A.; Mascitelli, Justin R.; Wilson, Natalie; Stein, Laura; Liang, John; Turkheimer, Lena M.; Morey, Jacob R.; Schwegel, Claire; Awad, Ahmed J.; Shoirah, Hazem; et al.
Abstract : Background and Purpose—: Endovascular recanalization treatment for acute ischemic stroke is a complex, time-sensitive intervention. Trip-and-treat is an interhospital service delivery model that has not previously been evaluated in the literature and consists of a shared mobile interventional stroke team that travels to primary stroke centers to provide on-site interventional capability. We compared treatment times between the trip-and-treat model and the traditional drip-and-ship model. Methods—: We performed a retrospective analysis on 86 consecutive eligible patients with acute ischemic stroke secondary to large vessel occlusion who received endovascular treatment at 4 hospitals in Manhattan. Patients were divided into 2 cohorts: trip-and-treat (n=39) and drip-and-ship (n=47). The primary outcome was initial door-to-puncture time, defined as the time between arrival at any hospital and arterial puncture. We also recorded and analyzed the times of last known well, IV-tPA (intravenous tissue-type plasminogen activator) administration, transfer, and reperfusion. Results—: Mean initial door-to-puncture time was 143 minutes for trip-and-treat and 222 minutes for drip-and-ship ( P <0.0001). Although there was a trend in longer puncture-to-recanalization times for trip-and-treat ( P =0.0887), initial door-to-recanalization was nonetheless 79 minutes faster for trip-and-treat ( P <0.0001). There was a trend in improved admission-to-discharge change in National Institutes of Health Stroke Scale for trip-and-treat compared with drip-and-ship ( P =0.0704). Conclusions—: Compared with drip-and-ship, the trip-and-treat model demonstrated shorter treatment times for endovascular therapy in our series. The trip-and-treat model offers a valid alternative to current interhospital stroke transfers in urban environments.